Impact of the 2008 Beijing Olympics on the risk of pregnancy complications. Issue 4 (3rd July 2016) - Assibey-Mensah, Vanessa; Liu, Kaibo; Thurston, Sally W.; Stevens, Timothy P.; Zhang, Junfeng; Zhang, Jinliang; Kane, Cathleen; Pan, Ying; Weinberger, Barry; Ohman-Strickland, Pamela; Woodruff, Tracey; Rich, David Q.
ABSTRACT: Taking advantage of the natural experiment of the 2008 Beijing Olympics (August 8 to September 24), when air pollution levels decreased by 13% to 60%, the authors assessed whether having ≥1 pregnancy month during the Olympics was associated with decreased risks of hypertensive disorders (HDs) and/or fetal-placental conditions (FPCs). Singleton births to mothers with ≥1 pregnancy month in 2008 or 2009 ( N = 56, 155) were included. Using generalized additive models, the authors estimated the risk of HDs and FPCs associated with (1) the 2008 Olympics compared with the same dates in 2009, and (2) increased mean ambient PM10 (particulate matter with an aerodynamic diameter <10 μm), NO2 (nitrogen dioxide), and SO2 (sulfur dioxide) concentrations during each trimester. However, no association between HDs or FPCs and having any trimester during the 2008 Olympic period was found. This may, in part, be due to a small number of pregnancy complications in this population.